STARS Model: An Instructional Approach for Enhancing Skill Sets of Engineering Students - Karthikeyan, P.; Abirami, A. M.; Thangavel, M. (Journal of Engineering Education Transformations, 2025)
The competencies of engineering students are measured through personal, interpersonal and communication skills. This work aims to improve these skills of engineering students through a Design Thinking course. The course involves a series of individual and team activities in the process of conceptual design modeling or prototype development, which in turn builds the skills and competencies of students. This paper proposes the unique Instructional Design model by organizing Solo, Team activities with Assessment and Reflection for improving the Skills (STARS) of students. The STARS model consists of questionnaire with 18 questions on design thinking skills, 8 on personal skills, 6 on interpersonal skills, and 5 on communication skills. Data is collected from each student after each assessment. The survey responses are analyzed and the attainment of skills are assessed using the Priority Need Index (PNI) method. It helps the instructor to focus more on specific skills in the forthcoming reviews. The experimental results proved that the proposed STARS model improves the skills of engineering students.